10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Objective This study compared the predictive power of SABIHA and 3CPO scores for 30-day mortality in acute heart failure (AHF). Materials and methods This study retrospective observational study included adult patients with AHF who in emergency department. The demographic data, clinical findings, laboratory results, and echocardiographic parameters of the patients were recorded. SABIHA and 3CPO scores were calculated using data obtained at the time of presentation. Results Data of 342 patients were analyzed, of whom 291 (85%) survived and 51 (15%) died. The median SABIHA score was found to be 2 (2-3) in the survivor group, whereas it was 3 (2-4) in the mortality group (p<0.001). Similarly, the median 3CPO score for the entire cohort was determined to be 2 (1-3). In the survivor group, the median 3CPO score was 2 (1-3), while it was 3 (2-4) in the 30-day mortality group (p=0.005). Multivariate analysis demonstrated that the SABIHA score was an independent predictor (p<0.001, odds ratio: 1.791 [1.298-2.47]), whereas the 3CPO score was not an independent predictor (p=0.184, odds ratio: 0.833 [0.637-1.09]). Conclusion The SABIHA score demonstrated superior performance in predicting 30-day mortality in patients with AHF compared to the 3CPO score. Therefore, the SABIHA score could assist as a successful tool on behalf of risk stratification in AHF cases.